Quality-of-life Outcomes after Sinus Surgery in Allergic Fungal Rhinosinusitis versus Nonfungal Chronic Rhinosinusitis. Issue 2 (March 2016) - Masterson, Liam; Egro, Francesco M.; Bewick, Jessica; Erskine, Sally E.; Clark, Alan; Javer, Amin R.; Philpott, Carl M.
Background: Given the differences in pathophysiology between allergic fungal rhinosinusitis (AFRS) and other chronic rhinosinusitis (CRS) subgroups, it remains unclear about whether these patients respond differently to a combination of surgical and medical treatments. Objective: To evaluate differences in quality-of-life (QoL) outcomes for a cohort of patients who underwent endoscopic sinus surgery (ESS) for CRS. Methods: This retrospective review included patients with CRS who underwent ESS between 2010 and 2013. QoL was measured by using the 22-item Sino-Nasal Outcome Test (SNOT-22). Variables collected included baseline demographics, SNOT-22 scores before ESS and at 1, 3, 6, 9, and 12 months after ESS. Groups tested were CRS with nasal polyposis, CRS without nasal polyposis (CRSsNP), and patients with AFRS. A linear mixed- effects regression model was used to calculate the adjusted mean QoL differences. Results: Among the 250 patients included, 61.6% had CRS with nasal polyposis (n = 154), 28.8% had CRSsNP (n = 72), and 9.6% had AFRS (n = 24). Significant differences were seen in SNOT-22 scores between pre- and postoperative visits and between the etiologic subgroups (p < 0.001). Multivariate analysis revealed significantly greater improvement in QoL for patients with AFRS in comparison with those with CRSsNP at the 9-month follow-up (change in SNOT-22 score, 22.6 [95% confidence interval, 1.2–44.1]; p < 0.0) and the 12-month follow-up (change in SNOT-22 score, 20.2 [95% confidence interval, 0.5–39.9]; p < 0.04). Conclusions: Patients with AFRS experienced a more-prolonged QoL benefit from surgical and targeted medical intervention compared with those with CRSsNP, which may reflect the severity of inflammation that they presented with compared with other CRS subtypes.